ToF‐SIMS study of the behavior of thermally oxidized films formed on nickel‐based 690 alloy in high‐temperature water. (3rd July 2012) - Mazenc, A.; Galtayries, A.; Seyeux, A.; Marcus, P.; Leclercq, S.
<x xml:space="preserve">Abstract</x> Alloy 690 is a high‐chromium nickel alloy widely used for steam generator tubes in pressurized water reactors. We have applied an optimized thermal oxidation treatment to alloy 690 consisting of 4 h at 500 °C (0.6 at% O2 in Ar) to make an improved diffusion barrier layer limiting the release of Ni during processing. The efficiency of such a treatment was tested by immersion in simulated pressurized water reactor primary water for 9 weeks. This work also explores the use of time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) to characterize the oxidized films formed after different treatments. Reference spectra were acquired by analyzing thermally oxidized Ni, Cr, and Ni‐30Cr samples as well as hydroxides and spinel powders [Ni(OH)2 and NiFe2O4]. ToF‐SIMS spectra of model oxides have allowed the selection of a set of ionic intensity ratios to be used for data processing of the spectra and profiles, obtained after the different oxidation steps applied on alloy 690. Thus, the following information was obtained: (i) the oxide layer structure is triplex; (ii) an intermediate layer is composed of Cr2O3, on which surface coverage depends on treatment; (iii) the outer layer is Ni‐ and Fe‐rich, whereas the inner layer is most probably constituted by a NiCr spinel oxide; and (iv) the total oxide layer grown during thermal oxidation is thinner than the one directly formed in primary water. If similar in thickness, the thermally grown oxide layer has a different composition once exposed to primary water. This ToF‐SIMS strategy was very fruitful in such a surface tube characterization. Copyright © 2012 John Wiley & Sons, Ltd.